Real-Life Data on the Efficacy of Canakinumab in Patients with Adult-Onset Still's Disease - Antonio Vitale; Virginia Berlengiero; Jurgen Sota; Luisa Ciarcia; Nicola Ricco; Sara Barneschi; Mariam Mourabi; Giuseppe Lopalco; Chiara Marzo; Francesca Bellisai; Florenzo Iannone; Bruno Frediani; et al. (Hindawi Limited, 2020)
Background. Interleukin-1 inhibition has revealed to be a successful treatment approach for patients with adult-onset Still's disease (AOSD). However, real-life experience is focused on the use of anakinra, while data about canakinumab (CAN) are mainly based on case reports and small case series. Patients and Methods. Patients classified with AOSD according to Yamaguchi criteria and treated with CAN were consecutively enrolled. Their clinical and therapeutic data were retrospectively collected and statistically analysed to assess the role of CAN as a therapeutic opportunity in AOSD patients in terms of clinical and laboratory disease control along with corticosteroid-sparing effect. Results. Nine AOSD patients (8 females and 1 male) treated with CAN for 15.00±12.3 months were enrolled. Resolution of clinical manifestations was reported in 8/9 cases at the 3-month assessment; a significant decrease in the number of tender joints (p=0.009), swollen joints (p=0.027), and disease activity score on 28 joints-C-reactive protein (DAS28-CRP) (p=0.044) was observed during the study period. The systemic score of disease activity significantly decreased at the 3-month and 6-month assessments and at the last visit compared to the start of treatment (p=0.028, p=0.028, and p=0.018, respectively). The daily corticosteroid dosage was significantly reduced at the 3-month and at the last follow-up visits (p=0.017 and p=0.018, respectively). None of the patients experienced adverse events or severe adverse events during the follow-up. Conclusions. CAN has shown prompt and remarkable effectiveness in controlling AOSD activity in a real-life contest, with a significant glucocorticoid-sparing effect and an excellent safety profile.